4‐Biphenylalanine‐ and 3‐Phenyltyrosine‐Derived Hydroxamic Acids as Inhibitors of the JumonjiC‐Domain‐Containing Histone Demethylase KDM4A. (9th August 2016) - Morera, Ludovica; Roatsch, Martin; Fürst, Michael C. D.; Hoffmann, Inga; Senger, Johanna; Hau, Mirjam; Franz, Henriette; Schüle, Roland; Heinrich, Markus R.; Jung, Manfred
Abstract: Overexpression of the histone lysine demethylase KDM4A, which regulates H3K9 and H3K36 methylation states, has been related to the pathology of several human cancers. We found that a previously reported hydroxamate‐based histone deacetylase (HDAC) inhibitor (SW55) was also able to weakly inhibit this demethylase with an IC50 value of 25.4 μm . Herein we report the synthesis and biochemical evaluations, with two orthogonal in vitro assays, of a series of derivatives of this lead structure. With extensive chemical modifications on the lead structure, also by exploiting the versatility of the radical arylation with aryldiazonium salts, we were able to increase the potency of the derivatives against KDM4A to the low‐micromolar range and, more importantly, to obtain demethylase selectivity with respect to HDACs. Cell‐permeable derivatives clearly showed a demethylase‐inhibition‐dependent antiproliferative effect against HL‐60 human promyelocytic leukemia cells. Abstract : Switching inhibitory activity : By starting from the reported histone deacetylase (HDAC) inhibitor SW55 (HDAC1 IC50 : 52.7 nm ; HDAC6 IC50 : 107.0 nm ), we were able, with broad structural modifications and also by exploiting the versatility of the radical arylation with aryldiazonium salts, to increase the inhibitory potency against the histone demethylase KDM4A into the low‐micromolar range (SW55 KDM4A IC50 : 25.4 μm ;16 p and16 r KDM4A IC50 : 6.8 μm ). More importantly, we were able to decrease, and for some compounds even abolish, histone deacetylase activity.